Reliable Path Selection in AODV: A QoS-Based Strategy for MANET - Dr.A. Kathirvel (Utilitas Mathematica, 2025)
This paper presents an enhancement to the Ad-hoc On-Demand Distance Vector (AODV) routing protocol by introducing a QoS Parameter-Based Reliable Path Selection (QRP-AODV) mechanism. The study focuses on optimizing packet transmission with minimal delay and assured delivery, achieved through link routine examination. The simulation is conducted using the Qualnet Simulator, demonstrating the improvements in Packet Delivery Ratio (PDR), end-to-end delay, average jitter, and routing overhead. The proposed model is compared with existing routing protocols such as NATCAD, EDAODV, LBT, and DRP, demonstrating superior performance in MANETs.